Beneath the Rhythm: Deciphering the Subtle Perforation of the Right Ventricle by a Pacemaker Lead - Munde, Kalyan; Paliwal, Mohan; Jain, Akshat (Jurnal Kardiologi Indonesia, 2024)
Cardiac perforation by the lead of permanent pacemaker implantation (PPM) devices is a critical complication that often occurs within 24 hours after the implantation but can occur later. Here we report a case of 82-year-old female patient with perforation of the right ventricular wall due to RV lead after 3 months of pacemaker implantation, which was managed conservatively.